Preparation and In Vitro Release of Drug-Loaded Microparticlesfor Oral Delivery Using Wholegrain Sorghum Kafirin Protein - Lau, E.; Johnson, Stuart; Stanley, R.; Mikkelsen, D.; Fang, Zhongxiang; Halley, P.; Steadman, K. (Hindawi Publishing Corporation, 2015)
Kafirin microparticles have been proposed as an oral nutraceutical and drug delivery system. This study investigates microparticles formed with kafirin extracted from white and raw versus cooked red sorghum grains as an oral delivery system. Targeted delivery to the colon would be beneficial for medication such as prednisolone, which is used in the management of inflammatory bowel disease. Therefore, prednisolone was loaded into microparticles of kafirin from the different sources using phase separation. Differences were observed in the protein content, in vitro protein digestibility, and protein electrophoretic profile of the various sources of sorghum grains, kafirin extracts, and kafirin microparticles. For all of the formulations, the majority of the loaded prednisolone was not released in in vitro conditions simulating the upper gastrointestinal tract, indicating that most of the encapsulated drug could reach the target area of the lower gastrointestinal tract. This suggests that these kafirin microparticles may have potential as a colon-targeted nutraceutical and drug delivery system.